Bidirectional causal relationship between obesity and osteoarthritis: Insights from a two-sample Mendelian randomization study - Anne Kamps; Jos Runhaar; Katerina Trajanoska; William D. Thompson; Weiya Zhang; Bahar Sedaghati-khayat; Joyce B.J. van Meurs; Sita M.A. Bierma-Zeinstra (Osteoarthritis and Cartilage Open)
Objective: Osteoarthritis (OA) is a prevalent chronic disease associated with disability worldwide, and obesity is a key modifiable risk factor for OA. The study's aim was to investigate the causal relationship between obesity and OA. Method: This study employed a two-sample Mendelian randomization (MR) approach to investigate the bidirectional causal relationship between obesity, using body mass index (BMI) as its proxy, and OA of the knee, hip, and hand. Genetic instruments were derived from large-scale GWAS meta-analyses, including ∼681,000 individuals for BMI and ∼827,000 individuals (177,000 OA cases) for OA. Inverse variance weighted with multiplicative random effects analysis was performed as primary analysis, and in addition sensitivity analyses relying on different assumptions were performed. Results: The MR analysis revealed that genetically predicted BMI had a causal effect on increased risk of knee (OR 1.91, 95 ​% CI 1.80–2.03), hip (OR 1.52, 95 ​% CI 1.41–1.64) and hand OA (OR 1.21, 95 ​% CI 1.04–1.23). Sensitivity analyses confirmed the robustness of these associations. However, there was no evidence for a causal effect from knee, hip or hand OA on BMI. Conclusion: This study provides strong evidence supporting a causal effect of obesity (measured by BMI) on OA, with a more pronounced effect in weight-bearing knee & hip joints compared to non-weight-bearing hand joint. There was no causal evidence for the reverse direction. Future research could look more in depth into differences in the genetic variants that may represent different biological underlying mechanisms.